2020
DOI: 10.1038/s41598-020-59436-y
|View full text |Cite
|
Sign up to set email alerts
|

Defining variation in pre-human ecosystems can guide conservation: An example from a Caribbean coral reef

Abstract: This file includesSupplemental radiometric dating methods figures S1 to S4 Tables S1 and S2References for supplementary material 1 Supplemental radiometric dating methods U-Th dating was conducted on coral fragments using a Nu Plasma multi-collector inductively-coupled plasma mass spectrometer (MC-ICP-MS) in the Radiogenic Isotope Facility at the University of Queensland, following chemical treatment procedures and MC-ICP-MS analytical protocols described in Clark et al. [1] . For U-Th dating, each coral sampl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 79 publications
1
12
0
Order By: Relevance
“…The paleontological S. pugilis remains (n=11 adult shells) were collected from a fossilized fringing reef excavated for construction purposes near the old town of Lennond (9°21’37.0” N 82°16’09.9” W; see Figure 1 ). Twenty four Uranium-Thorium and eight radiocarbon dates from 32 coral pieces date the reef at Lennond to the mid-Holocene (Mean = 6507, SD = 407, Min = 5711, Max = 7187 years BP; Fredston-Hermann et al, 2013; Lin et al, 2019; O’Dea et al, 2020; Dillon et al, in submission). This predates the earliest evidence of human interactions with marine species in the region which starts around around 4000 BP (Baldi, 2011), and confirms previous conclusions that the Caribbean slope of Panama was prehistorically not extensively populated until the Late Holocene (Griggs, 2005; O.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The paleontological S. pugilis remains (n=11 adult shells) were collected from a fossilized fringing reef excavated for construction purposes near the old town of Lennond (9°21’37.0” N 82°16’09.9” W; see Figure 1 ). Twenty four Uranium-Thorium and eight radiocarbon dates from 32 coral pieces date the reef at Lennond to the mid-Holocene (Mean = 6507, SD = 407, Min = 5711, Max = 7187 years BP; Fredston-Hermann et al, 2013; Lin et al, 2019; O’Dea et al, 2020; Dillon et al, in submission). This predates the earliest evidence of human interactions with marine species in the region which starts around around 4000 BP (Baldi, 2011), and confirms previous conclusions that the Caribbean slope of Panama was prehistorically not extensively populated until the Late Holocene (Griggs, 2005; O.…”
Section: Methodsmentioning
confidence: 99%
“…By measuring the height, width, and lip thickness of S. pugilis shells from archaeological Sitio Drago (dated to AD 690-1410; Wake 2006; Wake et al 2012, 2013), paleontological shells from a mid-Holocene fringing coral reef at Lennond (Fredston-Hermann et al, 2013; Lin et al, 2019; O’Dea et al, 2020), and modern sites spaced throughout the Bocas del Toro archipelago, O’Dea et al (2014) found that size at sexual maturity has decreased consecutively from the paleontological ‘pre-human’ period to the archaeological deposits to the present day. This size decrease is associated with a decline in edible meat weight by ~40% over the past 7,000 years (O’Dea et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While heavily impacted and increasingly degraded now, coral reefs have been resilient to past sea‐level and temperature fluctuations over long timescales (Greer et al., 2009; Webster et al., 2018). Therefore, understanding the development of ancient coral reefs and their responses to natural environmental change is helpful to aid protection of presently healthy reefs and to restore degraded reefs in future (Humblet & Webster, 2017; Kuffner & Toth, 2016; Odea et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…All of these characteristics increase the chance that waters will stratify and surface oxygen will fail to diffuse or become mixed into benthic waters (Diaz and Rosenberg 2008). The increasing eutrophication from runoff of nutrients that has been observed in the region (Seemann et al 2014), likely caused by deforestation and fertilization from local banana plantations and other human effluents (Stephens 2008, Cramer 2013, Aronson et al 2014, Graniero et al 2016, O'Dea et al 2020, could explain the perceived increased frequency of hypoxia in the bay. Alternatively, episodic hypoxic events may have naturally occurred for millennia, and simply been unobserved due to the lack of long-term proxy data and ephemerality of hypoxia.…”
Section: Introductionmentioning
confidence: 99%